2018
DOI: 10.1177/2309499018778325
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of bone mineral density in the femoral heads of unstable intertrochanteric fractures

Abstract: The BMD was higher in the center region of the femoral head than in the inferior region. Therefore, lag screws are recommended to be inserted into the center of the femoral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…[ 28 ] On the contrary, some authors argued that the stability of the lag screw was correlated with the bone quality around the screw. [ 29 ] They measured the BMD with micro-computed tomography and found that it was higher in the center region of the femoral head than in the inferior region. Therefore, lag screws are recommended to be inserted into the center of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] On the contrary, some authors argued that the stability of the lag screw was correlated with the bone quality around the screw. [ 29 ] They measured the BMD with micro-computed tomography and found that it was higher in the center region of the femoral head than in the inferior region. Therefore, lag screws are recommended to be inserted into the center of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…(20) It was thought that this situation could be caused as a result of the relatively low bone mineral density of the anterior and posterior region of the femoral head reported in previous studies. (21) However, studies that investigated the relationship of the intramedullary position of the implant with cut-out are few and there are contradictions between the results of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, lumbar vertebral or proximal femoral BMD is quantified using dual-energy X-ray absorptiometry-the procedure recommended by the World Health Organization and by several guidelines [1][2][3]. Yet, BMD assessment in other specific regions is also important as it can be used for surgical planning to achieve good clinical results; to this end, studies have used quantitative computed tomography (CT) images to determine local BMD in the proximal femur [4], femoral head [5,6], and the distal radius [7].…”
Section: Introductionmentioning
confidence: 99%